INTEGRASI HARGA BAWANG MERAH PADA PASAR GERBANG RAJA DAN PASAR LOA KULU KABUPATEN KUTAI KARTANEGARA - Drianti, Astik; Nugroho, Agung Enggal; Santra, Santra (Agriculture Faculty, University of Kutai Kartanegara, Indonesia, 2018)
Red onion market integrated on Gerbang Raja and Loa Kulu Market Kutai Kartanegara Regency, was to determine red onion margin exsisting and to known market integrated between Gerbang Raja market and Loa Kulu market used correlation and determination coefficient.This research showed, average margin at Gerbang Raja market was Rp. 5.800, and Rp. 4.213 at Loa Kulu market. Both market have a weak relation, it is show by correlation coefficient r = 0,44803, wich is mean both market does not have any relation in puchace of source. Keywords : Integration market, Margin, Red onion